Being active Muslim audiences: reception of Thai films in Indonesia. Issue 4 (17th September 2021) - Rosidi, Imron
Abstract : Most studies on media in Indonesia have tended to support the concept of passive audiences. This article aims to explain the reception of young Muslims in Thai films. Thai films are consumed by young Indonesian Muslims recently. The research question proposed is how these Muslim audiences respond and interpret messages and representations of Thai films and the extent to which their Islamic background affects this reception. This article employs interviews and observations to gather data. This study finds that the consumption of young Indonesian Muslims in Thai films supports the concept of active audiences because audiences can select those products based on their interest. These more active audiences use laptops or mobile phones to watch Thai films they like. Furthermore, Indonesian youth do not passively receive all representations of Thai films. This study recommends two points. First, in this global era, the restrictions of consumption on foreign cultural products, both from religious and state authority, are unnecessary. This is because audiences can select and negotiate representations of cultural products. Second, television stations need to provide a new medium in which audiences can actively choose television programs based on their own schedule, not a fixed schedule decided by the television producer.